Evaluating the Polarization of Tumor-Associated Macrophages Into M1 and M2 Phenotypes in Human Cancer Tissue: Technicalities and Challenges in Routine Clinical Practice - Jayasingam, Sharmilla Devi; Citartan, Marimuthu; Thang, Thean Hock; Mat Zin, Anani Aila; Ang, Kai Cheen; Ch'ng, Ewe Seng (Frontiers in oncology, 2020)
Tumor-associated macrophages (TAMs) as immune cells within the tumor microenvironment have gained much interests as basic science regarding their roles in tumor progression unfolds. Better understanding of their polarization into pro-tumoral phenotype to promote tumor growth, tumor angiogenesis, immune evasion, and tumor metastasis has prompted various studies to investigate their clinical significance as a biomarker of predictive and prognostic value across different cancer types. Yet, the methodologies to investigate the polarization phenomena in solid tumor tissue vary. Nonetheless, quantifying the ratio of M1 to M2 TAMs has emerged to be a prevailing parameter to evaluate this polarization phenomena for clinical application. This mini-review focuses on recent studies exploring clinical significance of M1/M2 TAM ratio in human cancer tissue and critically evaluates the technicalities and challenges in quantifying this parameter for routine clinical practice. Immunohistochemistry appears to be the preferred methodology for M1/M2 TAM evaluation as it is readily available in clinical laboratories, albeit with certain limitations. Recommendations are made to standardize the quantification of TAMs for better transition into clinical practice and for better comparison among studies in various populations of patients and cancer types.